Multi‐spurious harmonics suppression in folded hairpin line bandpass filter by meander spur‐line. Issue 11 (13th August 2021) - Das, Tarun Kumar; Chatterjee, Sayan
ABSTRACT: The present article exhibits the improvement in wide stopband harmonic suppression techniques of fourth‐order compact hairpin‐line Chebyshev type narrowband (4%) bandpass filter centered at 2.5 GHz by meander spur‐line. Initially, the compactness of 42% over the conventional hairpin‐line cell has been achieved by folding the open‐end arms of the hairpin line to folded hairpin‐line cell. Accordingly, the improvement of the skirt characteristics and the shifting of the harmonics to higher frequencies have been observed with the cost of harmonics attenuation levels' degradation. Subsequently, an improvement in the stopband rejection level of 40 dB up to 4 f 0 has been achieved by incorporating meander spur‐line to all the coupled edges of the adjacent folded cells of the compact filters along with compactness of 38%.